Gamification a way to Improve Social Management and Self-efficacy (2023)
ABSTRACT : This action-research aimed improving student’s self-efficacy and social management thought the gamification approach. It was conducted in a public school in La Ceja del Tambo in Antioquia with 34 seven graders. Action strategies included the implementation of a gamification system with games, points and rewards, visual marks, and a leaderboard. Data gathering instruments included teacher’s journal, questionnaires, surveys, teachers’ reflections, and video recordings, Findings referred to playing an assuming roles help students to solve conflicts and the reflection process helps students become aware of their abilities.